A Notorious Example of Failed Mindreading: Dramatic Irony and the Moral and Epistemic Value of Art - Clifton, Scott (The Journal of aesthetic education, 2016)
The act of mindreading has been recognized to have great moral and epistemic value. Unfortunately, psychological research has shown that we are naturally inaccurate at mind reading, which should worry us quite a bit. It has also been shown that, when motivated to mindread well, subjects become more accurate. In this paper, I argue that some kinds of artwork--specifically, those utilizing dramatic irony--can educate us as to how valuable accurate mindreading is and motivate us to try to mindread well. The primary example I discuss is Alfred Hitchcock's film Notorious. OA